The Prevalence and Subtype Distribution of Hepatitis C Virus Infection among Hemodialysis Patients in a Private Hospital in Surabaya, Indonesia - MOCHAMAD AMIN; JUNIASTUTI .; TAKAKO UTSUMI; YOSHIHIKO YANO; MOCHAMAD YUSUF; MOCHAMMAD THAHA; PRIYO BUDI PURWONO; RETNO HANDAJANI; SOETJIPTO .; HAK HOTTA; YOSHITAKE HAYASHI; MARIA INGE LUSIDA (Microbiology Indonesia, 2012)
The prevalence of hepatitis C virus (HCV) infection has been as high as approximately 80% in patients with maintenance hemodialysis in public hospitals in Indonesia. However, the prevalence in private hospitals has not been examined yet. The aim of  this study was  to  investigate  the prevalence of anti-HCV antibody and  the subtype distribution in patients with hemodialysis in a private hospital in Surabaya, Indonesia. Sera were obtained from 41 hemodialysis patients in a private hospital in Surabaya. The positive prevalence of anti-HCV antibody was carried out by  the enzyme-linked  immunosorbent assay (ELISA). Anti-HCV-positive sera were subjected  to  reverse transcription-PCR (RT-PCR) to detect HCV RNA and then direct sequencing. The HCV subtype was examined by phylogenetic analysis. Twenty five patients (61%) out of 41 were positive for anti-HCV antibody, and HCV-RNA was detected in 19 patients. The positive prevalence of anti-HCV antibody was 7.7% (one out of 13 patients) among patients who had undergone hemodialysis  for  less  than one year, whereas  it was 85.7%  (24 out of  28  patients)  among  patients who  had  undergone  hemodialysis  for  over  one  year.  Phylogenetic  analysis revealed HCV-1a  (52.6%) was  the most common  subtype,  followed by 1b  (15.8%), 1c  (15.8%), 2a  (5.3%), and 3k (5.3%). In conclusion,  the prevalence of HCV  infection among hemodialysis patients  in a private hospital was as high as  that  in general hospitals. The predominant subtype was HCV-1a, which  is  in accordance with  the previous studies  in general hospitals  in Surabaya,  Indonesia.